Islam on Screen: Talk Shows' Portrayals During Indonesia's 2024 Election at tvOne and CNN Indonesia - Syaiful Halim; Zaenal Mukarom; Moch. Fakhruroji (UIN Sunan Gunung Djati Bandung, 2026)
This study explores the representation of Islam in political talk shows on two major Indonesian news television stations—tvOne and CNN Indonesia—during the lead-up to the 2024 Presidential Election. Using a qualitative approach and document analysis method, the research focuses on two episodes that exemplify how Islamic identity is framed: Catatan Demokrasi from tvOne and Political Show from CNN Indonesia. Guided by Halliday’s social semiotics and Hall’s theory of representation, the analysis investigates both audio-visual content and discursive structures to reveal underlying patterns of meaning. The findings show that Islam is often reduced to a socio-political identity marker attached to certain political figures rather than explored as a religious or philosophical system. Such framing, recurrently amplified by hosts and guests, leads to the oversimplification and banalization of Islamic identity in mainstream media. While political identity and religious symbolism appear repeatedly in these discussions, the programs lack theoretical clarity and depth regarding the concept of identity politics. The study contributes to media and communication studies by offering a critical reflection on the media’s role in shaping public perceptions of Islam. It also proposes a new way to conceptualize televised representation by emphasizing the ethical implications of religious commodification during electoral periods. The research calls for a more responsible media practice that upholds the integrity of religious identity and fosters inclusive political discourse.